PARENTING A CHILD WHO IS MISUSING ILLEGAL SUBSTANCES: STRENGTHENING FATHERHOOD - Matheba, Mmathato Calphurnia; Kgadima, Phuti; Mabelane, Keatlegile Winne (Social Work/Maatskaplike Werk, 2021)
A qualitative study was undertaken with 13 participants to understand the challenges experienced by fathers who are parenting children misusing illegal substances. The sample was selected through purposive and snowball sampling. Data were gathered through semi-structured interviews and analysed thematically. Principles of credibility, transferability, dependability and confirmability were utilised for data verification. A fatherhood–masculinity model guided this study. Fathers are often socialised to exercise a particular notion of masculinity, which may limit their engagement with their children. However, findings in this study established that fathers are equally capable of active parenting. Therefore, an awareness of the unique contributions of fathers and supporting them in their role is important.